Planning With Timetable Supplements in Railway Timetables - Schittenhelm, Bernd (Proceedings from the Annual Transport Conference at Aalborg University, 2011)
The use of time supplements in railway timetables is a trade of between attractive travel times and punctuality levels. Punctuality is a key performance indicator for timetables and time supplements are therefore applied in any timetable. Time supplements can be found as running time supplements, dwell time supplements and buffer times between trains. These are described in the paper. Through analyzing the present valid timetable it is shown that the present size of running time supplements is approximately 50% bigger as recommended by the UIC. Unreliable input data for the timetabling process can be a valid reason for unnecessary high time supplement levels in the timetable. Making the best use of the applied running time supplement has resulted in several application strategies. Several are presented in the paper. A Danish success story is the use of condensation and compensation zones on the Copenhagen suburban railway network. This is inspired by the approach used in the Swiss Bahn2000 timetable for station hubs. A political demand for future travel times not higher than or below one hour between the cities of Copenhagen and Odense leads to an investigation of 3 possible scenarios: Applying the existing planning rules in regards to time supplements, using the recommendations from the UIC or making a compromise by adapting the existing rules to fulfill the political demands. It is shown that the existing planning rules cannot provide the necessary reduction in travel time. Critical low levels of running time supplements are the result when using UIC recommendations. A compromise can be the solution. This demands a halving of the presently applied running time supplements and therefore also a new approach to timetabling and railway operation in Denmark.